Event-Related Potentials in Global-Local Processing: Lateralization, Parallel Processing and the Effect of Unattended Variability - Evans, Maureen (My University, 1998)
An object in the visual field can be perceived as a whole and as the parts from which the whole is composed. Early investigations into whole-part processing led to the hypothesis that the global aspect, the whole, is processed before the local aspects, the parts. However, recent electrophysiological work shows that in the early stages of processing, the global and local levels of an object are processed in parallel. In addition, a processing asymmetry exists in that the right hemisphere is biased for global level processing whereas the left hemisphere is biased for local level processing. In an ERP study, I examined the lateralization and time-course of global-local processing in normal adult humans and found further evidence for lateralized, parallel processing of global-local stimuli. More importantly, I found that task demands affected the latencies at which lateralized differences between the two levels emerged: a condition in which interference from one level on the other was minimal showed very early, lateralized attentional effects (80 ms). In a relatively more demanding condition, lateralization of global and local processing was not evident until 200-350 ms. One possible explanation is that as the influence of distractors at the unattended level increases, resources in both hemispheres are engaged. To corroborate these findings, I included conditions in which subjects were required to switch attention among levels and visual fields: Evidence for lateralization and parallel processing persisted. Moreover, the additional load placed on the system by the switching conditions was apparent at the N1 component and support for right hemisphere attention switching mechanisms was obtained.
Processing of Global and Local Stimuli: an ERP Study
Keywords: unattended variability; lateralization; parallel processing; event-related probability